2023
DOI: 10.1038/s41467-023-40082-7
|View full text |Cite|
|
Sign up to set email alerts
|

Mitochondria-derived peptide SHLP2 regulates energy homeostasis through the activation of hypothalamic neurons

Abstract: Small humanin-like peptide 2 (SHLP2) is a mitochondrial-derived peptide implicated in several biological processes such as aging and oxidative stress. However, its functional role in the regulation of energy homeostasis remains unclear, and its corresponding receptor is not identified. Hereby, we demonstrate that both systemic and intracerebroventricular (ICV) administrations of SHLP2 protected the male mice from high-fat diet (HFD)-induced obesity and improved insulin sensitivity. In addition, the activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…SHLPs 1-6 comprise a class of rather recently discovered peptides, the functions of at least some of which are similar to those of HN and are currently under investigation [47,48]. As recently reported, SHLP2 has shown potent metabolic benefits through its activity on pro-opiomelanocortin neurons in the hypothalamus of the central nervous system [49]. Many other currently uncharacterized MDPs may exist [45].…”
Section: Hn and Hn-like Mitochondrial-derived Peptidesmentioning
confidence: 95%
“…SHLPs 1-6 comprise a class of rather recently discovered peptides, the functions of at least some of which are similar to those of HN and are currently under investigation [47,48]. As recently reported, SHLP2 has shown potent metabolic benefits through its activity on pro-opiomelanocortin neurons in the hypothalamus of the central nervous system [49]. Many other currently uncharacterized MDPs may exist [45].…”
Section: Hn and Hn-like Mitochondrial-derived Peptidesmentioning
confidence: 95%
“…In addition to humanin, Cobb et al identified 6 putative mitochondrial sORFs in 16S rRNA and named them small humanin-like peptides 75 . The SHLP family members exhibit distinct expression patterns and play different biological roles 77 ; for example, SHLP2 is involved in energy homeostasis 82 , SHLP3 is involved in cell survival 80 , and SHLP6 is involved in apoptosis 80 .
Fig.
…”
Section: Mitochondria-derived Peptides As Mitochondrial Messengersmentioning
confidence: 99%
“…In addition, species such as the gray squirrel ( Sciurus carolinensis ) having size variants encoded by mitochondrial and nuclear DNA, are promising models. In vivo experimentation could focus on the metabolic outcome of the 9mer of SHLP6 administered exogenously ( Merry et al, 2020 ; Kim et al, 2023 ).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…They promote cell proliferation [SHLP4 ( Cobb et al, 2016 )], improve cell viability, reduce cell apoptosis, and share protective effects with Humanin [SHLP2 and SHLP3 ( Cobb et al, 2016 )]. SHLP2, in addition, promotes thermogenesis in interscapular brown adipose tissue ( Kim et al, 2023 ). SHMOOSE boosts mitochondrial oxygen consumption, modifies energy signalling and metabolism in the central nervous system as well as reduces mitochondrial superoxide production ( Miller et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%